Establishing Haematological Parameters Of Captive Asian Elephant (Elephas Maximus) In Malaysia - Ahmad Naimie Mohammad Azlan (2024)
In Malaysia, Asian elephants play a significant role in the history and culture of the nation. Interpreting haematology and blood chemistry data for Asian elephants (Elephas maximus) can be challenging due to the wide range of reference values available. This study examined the haematological and serum biochemical parameters of elephants across different age stages, including infants (0-5 years), juveniles (5-10 years), sub-adults (11-15 years), and adults (16 years and above), with a focus on sex differences. In the juvenile group, most haematological parameters showed no significant (p> 0.05) differences between males and females. There were no significant (p>0.05) differences in most haematological parameters found in the adult group. For serum biochemical parameters, juvenile males had significantly (p<0.05) higher total protein levels than females, but other parameters such as ALT, ALP, LDH, and cholesterol showed normal values in both sexes. Sub-adult females demonstrated consistent biochemical profiles, with no significant (p>0.05) variation in parameters such as ALT, ALP, and cholesterol. In adults, most biochemical parameters did not differ significantly (p>0.05) between sexes, but globulin levels were significantly (p<0.05) higher in males. These results suggest that, while some sex-based variations exist, they do not consistently affect the haematological and biochemical profiles across different age groups in elephants. Keywords: haematology, serum biochemistry, elephants, sexes, age, infant, juvenile, sub-adult, adult